Đới động lực đứt gãy Tân kiến tạo và các tai biến địa chất liên quan tại Bắc Trung Bộ - Thơm, Bùi Văn (Vietnam Journal of Earth Sciences, 2005)
The dynamic zones of faults in North Central part of Vietnam had been determined from the analysise of lineaments and geomorfology, three conjugate fracture systems, anomalious of denudation in the surface and variation of geothem. The role of dynamics zones of fault in the relation with geological process (Earthquakes, land slide, Cracks in tthe ground and mineral water source ... ) had been analyzed.